2003
DOI: 10.1377/hlthaff.22.3.122
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence Of Treated And Untreated Mental Disorders In Five Countries

Abstract: We analyzed survey data from Canada, Chile, Germany, The Netherlands, and the United States to study the prevalence and treatment of mental and substance abuse disorders. Total past-year prevalence estimates range between 17.0 percent (Chile) and 29.1 percent (U.S.). Many cases are mild. Although disorder severity is strongly related to treatment, one- to two-thirds of serious cases receive no treatment each year. Most treatment goes to minor and mild cases. Undertreatment of serious cases is most pronounced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
171
1
13

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 286 publications
(198 citation statements)
references
References 15 publications
13
171
1
13
Order By: Relevance
“…Need factors, such as having a diagnosed mental disorder or suffering from more severe mental health problems, have indeed been identified as the most important predictors of utilization in different countries (e.g., Burns et al 2003;Leaf et al 1988;Parslow and Jorm 2000;Schomerus et al 2012). However, predisposing and enabling factors -such as female gender (Angst et al 2005;Bijl et al 2003;Bovier et al 2001;Burgess et al 2009;Fleury et al 2014;Wang et al 2007), higher educational level (Bijl and Ravelli 2000;Kovess-Masfety et al 2007;Parslow and Jorm 2000;Schomerus et al 2012;Wang et al 2007), more positive attitudes towards help-seeking (ten Have et al 2010) and having health insurance (e.g., Garfield et al 2011) -have repeatedly been shown to increase the likelihood of using mental health services even after adjusting for need.…”
Section: Introductionmentioning
confidence: 99%
“…Need factors, such as having a diagnosed mental disorder or suffering from more severe mental health problems, have indeed been identified as the most important predictors of utilization in different countries (e.g., Burns et al 2003;Leaf et al 1988;Parslow and Jorm 2000;Schomerus et al 2012). However, predisposing and enabling factors -such as female gender (Angst et al 2005;Bijl et al 2003;Bovier et al 2001;Burgess et al 2009;Fleury et al 2014;Wang et al 2007), higher educational level (Bijl and Ravelli 2000;Kovess-Masfety et al 2007;Parslow and Jorm 2000;Schomerus et al 2012;Wang et al 2007), more positive attitudes towards help-seeking (ten Have et al 2010) and having health insurance (e.g., Garfield et al 2011) -have repeatedly been shown to increase the likelihood of using mental health services even after adjusting for need.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the probability of seeking treatment is strongly related to the severity of the psychological disorder (Bijl et al, 2003). With respect to the relation between PTSD and health services utilization, Elhai, North, and Frueh (2005) demonstrated that most studies found that PTSD diagnoses were related to increased mental health services (MHS) utilization.…”
mentioning
confidence: 99%
“…17,18 Slechts de helft van de volwassenen met een depressieve stoornis wordt echter als zodanig in de huisartspraktijk herkend en behandeld. 19 Het gebruik van screeningsinstrumenten kan de huisarts ondersteunen bij het signaleren van (subklinische symptomen van) angst en depressie. 12,[20][21][22][23] Screenen kan op twee manieren plaatsvinden: .…”
Section: Inleidingunclassified
“…Dat zou dan in overeenstemming zijn met eerdere bevindingen, namelijk dat, ook al zijn huisartsen mogelijk extra alert, een groot deel van de volwassenen met een depressieve stoornis in Nederland blijkbaar niet wordt opgespoord. 19 Een beperking van ons onderzoek is de gebruikte terminologie in de vragenlijst. Voor het meten van de begrippen screenen, extra alert zijn en ongevraagd adviseren konden geen gevalideerde vragenlijsten worden gebruikt.…”
Section: Beperkingenunclassified